The Rhetoric of Lithuanian MeToo Discourse - Gabrėnaitė, Eglė; Triaušytė, Monika (Information & Media, 2021)
The great spread of the phenomenon of MeToo, a global movement promoting the publicity of the facts of sexual harassment, has also received a response in Lithuania: anonymous stories in blogs have grown into a provocative discourse that has attracted a great deal of attention. The aim of the research presented in this article is to characterise the discourse of MeToo in terms of rhetorical expression that has not been discussed yet: to identify and elicit the dominant elements of rhetorical argumentation.The empirical research was conducted using the method of rhetorical analysis that allows distinguishing and defining in rhetorical categories the models characteristic to rhetoric appeals. The method of rhetorical analysis combined with directed content analysis, as well as with critical discourse analysis. Following the methodology of provocative narrative research, it was analysed the material published at the time of maximum intensity and involvement in the discourse, such as testimonies, publications, interviews, and comments of women who have been subjected to sexual harassment.The results of rhetorical discourse analysis allow us to discuss the culture of accusation in which the normalization of victim condemnation is prevalent, and logical reasoning gives way to prejudice-based emotional appeals.
Keywords: metoo; rhetoric; provocative discourse